2011
DOI: 10.1021/bi1014002
|View full text |Cite
|
Sign up to set email alerts
|

The Amyloid Precursor Protein C-Terminal Fragment C100 Occurs in Monomeric and Dimeric Stable Conformations and Binds γ-Secretase Modulators

Abstract: The amyloid-β (Aβ) peptide is contained within the C-terminal fragment (β-CTF) of the amyloid precursor protein (APP) and is intimately linked to Alzheimer's disease. In vivo, Aβ is generated by sequential cleavage of β-CTF within the γ-secretase module. To investigate γ-secretase function, in vitro assays are in widespread use which require a recombinant β-CTF substrate expressed in bacteria and purified from inclusion bodies, termed C100. So far, little is known about the conformation of C100 under different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
36
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 21 publications
3
36
1
Order By: Relevance
“…C99 is known to dimerize through APPTM and is present in both monomer and dimer forms 24,31,37 . Barrett et al chose to solve the monomer structure of C99 in lyso-myristoylphosphatidylglycerol (LMPG) micelles and primarily focused on the cholesterol-binding properties of C99.…”
Section: Discussionmentioning
confidence: 99%
“…C99 is known to dimerize through APPTM and is present in both monomer and dimer forms 24,31,37 . Barrett et al chose to solve the monomer structure of C99 in lyso-myristoylphosphatidylglycerol (LMPG) micelles and primarily focused on the cholesterol-binding properties of C99.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there has been no consensus as to what is the binding site of NSAID-based GSMs. Some studies report that these compounds interact with APP-derived C99 fragment (25)(26)(27), whereas others have challenged this hypothesis (28 -31). Our data, showing that R-flurbiprofen and sulindac sulfide affect A␤ but not N␤ production, indicate that APP is the target of NSAID-based GSMs.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds, which are generally structurally distinct from the NSAID family by the absence of an acidic carboxyl group, are more potent and efficient in the central nervous system than were the early GSMs (21)(22)(23)(24). Some studies reported NSAID-based GSMs interacting with APP-derived C99 peptides (25)(26)(27), but other groups have challenged this implied substrate targeting hypothesis (28 -31). During the last year, we and others identified ␥-secretase instead of APP as the principal target of second generation GSMs (21,(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…Reports on the interaction between sulindac sulfide and the APP transmembrane sequence are, however, contradictory. Sulindac sulfide, among other ␥-secretase modulators, binds to the APP transmembrane sequence of the Cys 99 motif (23) and to Cys 100 dimers in the presence of SDS micelles (24). Bacterial reporter assays show that ␥-secretase modulators, including sulindac sulfide, bind to the GXXXG dimerization motif and, thereby, attenuate the dimerization of the APP transmembrane sequence (25), a process necessary for proteolytic cleavage (26).…”
mentioning
confidence: 99%